Interactive Learning for Water Pollution Awareness: A Game-Based Approach - Fatimah, Siti; Farida, Ida; Sukmawardani, Yulia (Heca Sentra Analitika, 2023)
This research explores the potential of interactive educational games as a tool to enhance environmental literacy, with a specific focus on water pollution issues. The study introduces a designed game encompassing various interactive modules, such as word games, drag-and-drop tasks, multiple-choice questions, evaluations, and an environmental literacy survey. The validation test was carried out by three validators consisting of material expert lecturers and media experts. The average rcount value for validation test results across material aspects, language aspects, and display (media) aspects was calculated as follows: 0.85, 0.92, and 0.84, resulting in an overall rcount value of 0.87. This overall value signifies high validity and strong interpretational significance. Furthermore, the feasibility test was carried out on 15 chemistry education students who had taken environmental chemistry courses. The average rcount of the feasibility test results from all aspects obtained a percentage value of 87%. This study highlights the importance of game design, evaluating long-term impacts, and integrating interactive games into educational curricula.